2019
DOI: 10.3390/polym11101710
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulose@ Activated Clay Nanocomposite with Hierarchical Nanostructure Enhancing the Removal of Aqueous Zn(II)

Abstract: A lignocellulose@ activated clay (Ln@AC) nanocomposite with a hierarchical nanostructure was successfully synthesized by the chemical intercalation reaction and applied in the removal of Zn(II) from an aqueous solution. Ln@AC was characterized by N2 adsorption/desorption isotherms and X-Ray Diffraction (XRD), scanning Electron Microscope (SEM), transmission Electron Microscopy (TEM) and Fourier Transform Infrared Spectroscopy (FTIR) analysis, and the results indicate that an intercalated–exfoliated hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Based on the literature, it has been observed that the use of hydrochloric acid (HCl) as an eluting agent seems to be a very effective desorbing agent compared to other eluting agents such as nitric acid, acetic acid, ethanol, etc. [85]. The adsorbents were dried after performing batch adsorption experiments and were considered as Li-loaded samples.…”
Section: + Recovery Examination By Desorption Experimentsmentioning
confidence: 99%
“…Based on the literature, it has been observed that the use of hydrochloric acid (HCl) as an eluting agent seems to be a very effective desorbing agent compared to other eluting agents such as nitric acid, acetic acid, ethanol, etc. [85]. The adsorbents were dried after performing batch adsorption experiments and were considered as Li-loaded samples.…”
Section: + Recovery Examination By Desorption Experimentsmentioning
confidence: 99%
“…There are multiple oxygen moieties (-OH, -COO, -C=O, C-O-C, etc.) in its molecular chains 20 . However, the adsorption capacity of unmodified LCS is relatively low, and LCS possesses low selectivity for adsorbates.…”
mentioning
confidence: 99%